A Review of Solid Medical Waste Management in Indonesian Hospitals - Anggreini Beta Citra Dewi; Aurina Firda Kusuma Wardani; Ervansyah Wahyu Utomo; Siti Rachmawati (Journal of Epidemiology and Public Health, 2026)
Background: Hospitals generate hazardous medical waste that threatens both environmental sanitation and human health. Common challenges include a lack of awareness, insufficient training, inadequate disposal infrastructure, and limited resources. Proper management is essential to minimize ecological impacts and prevent hospital-acquired infections (HAIs) at every stage—collection, segregation, transport, and storage. This study systematically evaluates global hospital waste management practices. Subjects and Method: This study is a systematic review  literature review conducted on  selected databases (PubMed, Science Direct, Google Schoolar) with a publication year between 2020 and 2025. Literature uses Indonesian and English. The literature included was literature with qualitative and quantitative method. The quality assessment of the literature was carried out using the JBI Critical Appraisal. Results: The research results from nine (9) articles related to solid medical waste management in Indonesia show that the process of sorting, transportation, temporary storage and final disposal in the management of medical waste from several hospitals has met the requirements in accordance with applicable regulations. Conclusion: While segregation and temporary storage show high compliance, final disposal remains a critical challenge due to incinerator licensing issues and third-party dependency. Addressing this requires practical staff training, routine audits, and a transition to alternative technologies like autoclaving. Strengthening contract governance and cost-benefit analysis between internal investment and outsourcing is essential for sustainable waste management in Indonesia.